2021
DOI: 10.3390/membranes11110827
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Foulant Ultrafiltration Polymer Composite Membranes Incorporated with Composite Activated Carbon/Chitosan and Activated Carbon/Thiolated Chitosan with Enhanced Hydrophilicity

Abstract: A rapid increase in population worldwide is giving rise to the severe problem of safe drinking water availability, necessitating the search for solutions that are effective and economical. For this purpose, membrane technology has shown a lot of promise but faces the challenge of fouling, leading to a reduction in its lifetime. In this study, ultrafiltration polyethersulfone membranes were synthesized in two different concentrations, 16% wt. and 20% wt., using the phase inversion method. Chitosan and activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…The highest flux for PES UF membranes has been shown by mAC filler added membranes which is in agreement with reported results [ 27 ]. The highly porous structure, large surface area and hydrophilic character of mAC makes the membranes more suitable candidate for UF process.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The highest flux for PES UF membranes has been shown by mAC filler added membranes which is in agreement with reported results [ 27 ]. The highly porous structure, large surface area and hydrophilic character of mAC makes the membranes more suitable candidate for UF process.…”
Section: Resultssupporting
confidence: 92%
“…The adsorption of BSA on the nanocomposite membrane surface was decreased because of electrostatic repulsion. In another study, AC, Chitosan and thiolated chitosan/AC has been seperately incorporated as filler in PES UF membranes to increase its hydrophilicity and reduce fouling [ 27 ]. The pure water flux and BSA flux both were high for AC added polymer composite membrane.…”
Section: Introductionmentioning
confidence: 99%
“…These results confirmed that the incorporation of chitosan in the PES matrix even in the presence of hydrophobic MWNTs could appreciably tune the hydrophilic character of the membrane samples. 39 As discussed in Section 3.8, the contact angle measurement results were related to the surface roughness values as measured from the AFM analysis.…”
Section: Contact Angle and Surfacementioning
confidence: 99%
“…However, chitosan membranes have low stability and mechanical strength. Therefore, it is necessary to modify their manufacturing process [ 28 , 29 ]. The addition of polyethylene glycol (PEG) and carbon nanotubes (CNT) has been shown to significantly increase the permeability and mechanical strength of chitosan membranes [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%